Factors associated with parental underestimation of child's weight status - Warkentin,Sarah (2018)
Abstract Objective The aim of this study was to examine the prevalence of parental misperception of child weight status, and identify socioeconomic, anthropometric, behavioral and dietary factors associated with underestimation. Method Cross-sectional study. Data was collected in 14 Brazilian private schools. Parents of children aged 2-8 years (n = 976) completed a self-reported questionnaire assessing their perception of their child's weight status, and sociodemographic, anthropometric, behavioral and dietary information. To measure the agreement between parental perception about child weight status and actual child weight status, the Kappa coefficient was estimated, and to investigate associations between parental underestimation and independent variables, chi-squared tests were performed, followed by multiple logistic regression, considering p ≤ 0.05 for statistical significance. Results Overall, 48.05% of the parents incorrectly classified their child's weight. Specifically, 45.08% underestimated their child's weight status, with just 3% of parents overestimating. Children with higher body mass index (OR = 2.03; p < 0.001) and boys (OR = 1.70; p < 0.001) were more likely to have their weight status underestimated by parents. Conclusion Since awareness of weight problems is essential for prevention and treatment, clinical practitioners should help parents at high risk of misperception to correctly evaluate their child's weight status.